Respuesta :
Answer:
Hi! I'll do my best to explain for you.
-6(2x-3)+2x =0 First, set the equation equal to zero.
-12x+18+2x=0 Then, distribute the -6 by multiplying it with the -2 and -3.
-10x+18=0 Combine the like terms, which are -12x and 2x, to get -10x.
-10x=-18 You want to get the x on 1 side. Subtract 18 from both sides.
x=-18/-10 Divide by -10 on both sides.
x=1.8 Simplify the fraction. The answer is x=1.8.
I hope this helped!
-6(2x-3) +2x
Distribute the -6 into the parentheses: -12x+18+2x
Combine like terms: -10x+18
Distribute the -6 into the parentheses: -12x+18+2x
Combine like terms: -10x+18